Sosialisasi Pembuatan Soal Ulangan Harian Dengan Menggunakan Google Form Pada Guru SMP 17 Padang - Elva, Yesri; Trisna, Novi; Jamhur, Annisak Izzaty (LPPM Universitas Dharma Andalas, 2024)
Google Form provides great benefits for teachers or teaching staff, namely Google Form, where Google Form is a service that makes it easy for users to carry out surveys and can even create exam questions. This online form is based on questions or questionnaires that can be customized by the creators. Google form is an effective and practical service for obtaining certain information. The Google form application is one application that is very useful in compiling a list of participant attendance. The things entered in the Google form include name, email, agency of origin, cellphone number, and other items that may be needed. Google Form is a component of the Google Docs service. This application is very suitable for students, teachers, lecturers, office workers and professionals who like making online quizzes, forms and surveys. By using this Google program, the teacher only needs to send a link to the students and then the students will answer questions directly on the Google form